PERANCANGAN SISTEM INFORMASI PERJALANAN DINAS PADA DINAS KETAHANAN PANGAN, TANAMAN PANGAN DAN HORTIKULTURA SUMATERA UTARA BERBASIS WEB - Rafli Bima Sakti (Bigint Computing Journal, 2024)
Official travel is a routine activity carried out by employees of the North Sumatra Food Safety, Food Crops and Horticulture Service in order to support the implementation of official duties and functions. The official travel administration process which is still carried out manually causes inefficiencies in data management and preparing official travel reports. To overcome these problems, this research aims to design a web-based Official Travel Information System for the North Sumatra Food Safety, Crop and Horticulture Service. The method used in this research is a descriptive method with a waterfall system development model. Needs analysis is carried out by observation, interviews and literature study. System design includes designing data, processes, interfaces and system architecture. The system was built using the PHP programming language, CodeIgniter framework, and MySQL database. The results of this research are a design for a web-based Official Travel Information System that can facilitate the official travel application process, manage official travel data, and create integrated official travel reports. With this system, it is hoped that management of official travel data can become more effective and efficient.